Flexible and Stretchable Electrically Conductive Polymer Materials for Physical Sensing Applications. (2nd January 2023) - Lin, Jui-Chi; Liatsis, Panos; Alexandridis, Paschalis
Abstract: Advances in stretchable and flexible sensors are responding to the emerging demand of wearable and portable smart electronics. A core component of these electronics are tactile sensing devices which detect external stimuli and obtain in-time information from the surroundings. A fusion of electronics, physics and materials science, tactile sensors have great potential in robots, biomedicine, flexible interactive devices, and several other applications. By integrating with a flexible polymer matrix conductive materials (nanometals, carbon nanomaterials, conducting polymers, etc.), which are either embedded in the matrix or surface-coated or sandwiched between films, the resulting conductive polymer-based composites are promising for flexible tactile sensors. This review summarizes recent advances across different types of tactile sensors, including piezoresistive, capacitive, piezoelectric, and triboelectric. Examples are highlighted on how the combination of new materials, unique structure designs, and novel fabrication methods can advance the progress of tactile sensors. Enhanced sensing performance and mechanical properties can be realized by integrating nanomaterials into polymer substrates. This review provides guidelines for further selection of polymer-based materials and design of tactile sensors.